ON THE ISSUE OF THE MAIN TYPES OF GRAMMATICAL AND STYLISTIC MISTAKES IN WRITTEN WORKS OF STUDENTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article, based on the richest factual material, typical types of grammatical and stylistic mistakes in written works of students are deeply analyzed.